Some convergence and data dependence results for various fixed point iterative methods - Karakaya, Vatan; Gursoy, Faik; Erturk, Muezeyyen (ELSEVIER, 2016)
We have compared rate of convergence among various iterative methods. Also, we have established an equivalency result between convergence of two recently introduced iterative methods and we have proven a data dependence result for one of them.
Keywords: Convergence; data dependence of fixed points; equivalence of convergence; iterative methods; rate of convergence; APPROXIMATION; Science & Technology - Other Topics